The effect of war on displaced hemodialysis patients in Sudan - Sara Mohamed Abdelgadir; Sufian Khalid Mohamed; Mohamed Osman Elamin; Wahaj A. Khan; Hatim O. Badri; Abdullah Muhammad Alzhrani; Osama Banah; Ahmad Salah Alkathiri; Ahmed A. Osman; Fowzi O. Elamin (Universa Medicina, 2026)
BACKGROUNDThe Sudan war has severely disrupted healthcare services, particularly for patients with end-stage renal disease (ESRD) dependent on regular hemodialysis. Conflict-related displacement, damaged infrastructure, medication shortages, and financial hardship have compromised dialysis continuity and patient outcomes. This study assessed the impact of war-related displacement on dialysis care among Sudanese hemodialysis patients. METHODSThis cross-sectional observational study included 101 displaced ESRD patients receiving maintenance hemodialysis. Data collection comprised demographic characteristics, causes of ESRD, dialysis access and adequacy, treatment interruptions, complications, medication availability, hospital admissions, and functional status before, during, and after the war. Comparisons of dialysis parameters and functional status before, during, and after the war were performed using Cochran’s Q test. RESULTSWar-related displacement was associated with statistically significant worsening of dialysis care. Dialysis frequency decreased from two to 1.5 sessions per week, and session duration declined from four to three hours (both p<0.05). Patients missed a median of one dialysis session per week. Consequently, out-of-pocket payment for medications surged from 42 (41.6%) pre-war to 93 (92.1%) during the war and persisted at 89 (88.1% in the current period (p<0.0001). Erythropoietin use declined from 98 (97.1%) to 39 (38.6%) (both at p<0.001). Displacement was also associated with significantly increased complications, hospitalizations, reduced medication adherence, and marked fatigue (p < 0.05). CONCLUSIONWar-related displacement significantly reduced dialysis adequacy, medication access, and continuity of care, resulting in increased morbidity. Immediate humanitarian and health-system interventions are essential to prevent excess mortality among displaced hemodialysis patients.